Integrating Resilience and Sustainability into Civil Engineering Projects - Field, Caroline; Zawislak, Chris; Harper, Ben; Davidson, Cliff Ian; Eide, Fran; Rosenberg, Heather; Hegelson, Jennifer; McNeil, Sue (American Society of Civil Engineers, 2023)
Integrating Resilience and Sustainability into Civil Engineering Projects, Infrastructure Resilience Publication 6, describes how the engineering community is working to integrate social science, policy, and economics into the planning, design, and management decisions surrounding physical infrastructure projects.
Keywords: Civil engineering -- Environmental aspects.; elektronické knihy; electronic books